Description of a new Hemigrammus Gill (Characiformes: Characidae) from the río Madeira basin in Peru and Bolivia - Ota, Rafaela P.; Lima, Flávio C. T.; Hidalgo, Max H. (Zootaxa, 2019)
We described herein a new Hemigrammus from the río Madre de Dios and rio Mamoré basins in southeastern Peru and Bolivia. The new species possess a color pattern similar to those belonging to the Hemigrammus lunatus species-group, i.e., a broad longitudinal dark stripe across the eye and a conspicuous, narrow dark stripe along the anal-fin basis. It can be easily diagnosed from the species belonging to this group by presenting the combination of the following characters: an oval, horizontally elongated humeral blotch, 6-7 upper branch and 10-12 lower branch gill-rakers, up to five cusps on broader maxillary teeth, and by lacking a midlateral dark stripe. Comments on its putative relationships are provided. Additionally, we updated the geographical distribution of Hemigrammus lunatus and H. machadoi based on an exhaustive survey of material deposited in collections. [Species Zoobank registration: urn:lsid:zoobank.org:act:A2ED5D61-8434-4A0F-BC5B-B496FB3DC191]